2016
DOI: 10.12740/app/63535
|View full text |Cite
|
Sign up to set email alerts
|

Schema modes in cluster B personality disorders

Abstract: SummaryAim: The present study aimed to investigate the role of schema modes in cluster B personality disorders. Materials and methods:The participants were 220 individuals -38 men and 137 women -selected from psychiatric and psychological clinics in Tabriz, Iran. Among the participants, 153 individuals were diagnosed with cluster B personality disorder (44 with borderline disorder, 16 with antisocial disorder, 56 with histrionic disorder and 37 with narcissistic personality disorder). The remaining 67 particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 23 publications
(51 reference statements)
0
3
0
Order By: Relevance
“…Having tendencies for unhealthy schema modes increases tendencies to develop anxiety disorders, drug addiction, depression, eating disorders, personality disorders, and chronic psychological disorders, as stated in many previous studies (Arntz et al, ; Giesen‐Bloo et al, ; Güneltay et al, ; Köse, ; Köse Karaca, ; Köse Karaca, ; Nordahl & Nysæter, ; Young, ). Furthermore, finding no significant difference between clinical and nonclinical groups in terms of bully and attack mode and enraged child mode may be because these two modes are mostly related to narcissistic and antisocial personality disorder (Dadashzadeh, Hekmati, Gholizadeh, & Abdi, ; Vos et al, ). Because the sample of the study was not composed of narcissistic and antisocial participants, the result was found parallel to the literature.…”
Section: Conclusion Discussion and Suggestionsmentioning
confidence: 99%
“…Having tendencies for unhealthy schema modes increases tendencies to develop anxiety disorders, drug addiction, depression, eating disorders, personality disorders, and chronic psychological disorders, as stated in many previous studies (Arntz et al, ; Giesen‐Bloo et al, ; Güneltay et al, ; Köse, ; Köse Karaca, ; Köse Karaca, ; Nordahl & Nysæter, ; Young, ). Furthermore, finding no significant difference between clinical and nonclinical groups in terms of bully and attack mode and enraged child mode may be because these two modes are mostly related to narcissistic and antisocial personality disorder (Dadashzadeh, Hekmati, Gholizadeh, & Abdi, ; Vos et al, ). Because the sample of the study was not composed of narcissistic and antisocial participants, the result was found parallel to the literature.…”
Section: Conclusion Discussion and Suggestionsmentioning
confidence: 99%
“…In Bach and Farrell (2018) study, for example, borderline personality disorder patients had higher scores in vulnerable, angry, and enraged child modes and the punitive parent mode than the healthy adult samples. Another study investigated the predictor schema modes of cluster B personality disorders (Dadashzadeh et al., 2016). The angry child mode was one of the predictors of borderline, antisocial, and narcissistic personality disorders, while the vulnerable child mode was only one of the predictors of borderline personality disorder.…”
Section: Anger Representations In the Context Of The Stmmentioning
confidence: 99%
“…In addition, those who suffer from HPD may refuse very intimate relationships to avoid potential negative stimuli (7). Other cognitive models suggest that maladaptive schemas are responsible for the development of personality disorders (9). Also, a combination of maladaptive schemas can explain the variance in PDs.…”
Section: Introductionmentioning
confidence: 99%